The universe behind barbed wire memoirs of a Soviet Ukrainian dissident - Marynovyč, Myroslav Frankovyč 1949- (University of Rochester Press, 2021)
"This is an English translation of a memoir by Myroslav Marynovich, a Ukrainian dissident who was imprisoned-and later exiled-during the Brezhnev years because of his membership in the Ukrainian Helsinki Human Rights Defense Group (UHG), which sought to make public the human rights conditions that existed in Soviet-controlled Ukraine. Born in Halychyna (a European-oriented western region of Ukraine, also known as Galicia) just after World War II, and educated in Soviet schools, the author describes in his memoir the influence of his Galician family in developing his position of resistance to totalitarian regimes. The narrative depicts life in Soviet-occupied Kyiv during the epoch of the Helsinki movement, describing the activities of the UHG and its members, their arrests, and the Soviet abuse of justice. The author shares details of the political prisoners' life in concentration camps and clarifies the circumstances of his exile to Kazakhstan. A significant amount of the memoir is dedicated to describing the author's personal spiritual growth; his perspective is that of a deeply religious person, a devoted Christian, and this, as one of the readers points out, is one of the features that makes his story noteworthy: "Marynovych belongs to another underrepresented group: dissidents driven by Christian faith who nonetheless joined the broader movement for civil and human rights - a movement dominated by secular, metropolitan intellectuals, many of them scientists of one kind or another." (The first underrepresented group, per this reader, is dissidents from Ukraine, of whom much less has been written about than their counterparts elsewhere in the Soviet Union.)
Keywords: Marynovyč, Myroslav Frankovyč -- 1949-; Ukraïnsʹka hromadsʹka hrupa spryjannja vykonannju Helʹsinksʹkych uhod; Dissident; Politischer Gefangener; Sowjetunion; Ukrainische SSR; Marynovych, Myroslav / 1949-; Dissenters / Ukraine / Biography; Human rights workers / Ukraine / Biography; Political prisoners / Ukraine / Biography; Intellectuals / Ukraine / Biography; Ukraïnsʹka hromadsʹka hrupa spryi͡anni͡a vykonanni͡u helʹsinksʹkykh uhod (Kyïv, Ukraine); Dissenters; Human rights workers; Intellectuals; Political prisoners; Ukraine; Biographies; Autobiografie